X-ray diffraction study of ferroelectric and antiferroelectric liquid crystal mixtures exhibiting de Vries SmA∗-SmC∗ transitions - VIJ, JAGDISH; MANNA, UTTAM; FUKUDA, ATSUO (My University, 2010)
In this Rapid Communication, results on smectic layer thickness, using synchrotron radiation x-ray diffraction, for different mixtures of ferroelectric and antiferroelectric liquid crystals are given. We find that with an increased ferroelectric component in the mixtures, the layer shrinkage at the de Vries SmA -SmC transition increases. This observation can be used to explain our previously observed behaviors U. Manna, J.-K. Song, Yu. P. Panarin, A. Fukuda, and J. K. Vij, Phys. Rev. E 77, 041707 2008 that the soft-mode dielectric strength decreases, the Landau coefficient increases, and the Curie-Weiss temperature range decreases with increased ferroelectric component in the mixture exhibiting de Vries SmA -SmC transition.
PUBLISHED
Keywords: Physics; Curie-Weiss temperature